Experimental Verification of a Numerical Model of RC Beam with CFRP Rope Strengthening - Szczecina, Michał; Tworzewski, Paweł; Bacharz, Kamil (Computer Assisted Methods in Engineering and Science, 2019)
This paper presents results of experimental tests and numerical analysis of reinforced concrete (RC) beams containing an additional carbon fibre rope strengthening. Two single-span RC beam specimens with classical reinforcing bars and stirrups and one carbon fibre rope as near-surface mounted (NSM) strengthening were tested in a four-point bending test. The paper presents and compares the results registered by the ARAMIS system during the test of two beams with carbon fibre rope under monotonic load with the results obtained in finite element analysis with Abaqus software using the concrete damaged plasticity model for concrete.